The optimal tax rule in the presence of time use - Jean Lim; Carolina Rodríguez-Zamora (Banco de México, 2010)
Using Mexican data on household time use and consumption, we find significant substitution between goods and time in home production and different elasticities of substitution for different household commodities. Adding these findings to the Ramsey optimal tax problem, we show it is optimal to impose higher taxes on market goods used in the production of commodities with a lower elasticity of substitution between goods and time. The reason is that government wants to minimize the distortionary substitution from market purchases toward untaxed time use in home production. This is an analog of the classical Corlett and Hague (1953-1954) result, differing in that we allow for the possibility of substitution between goods and time in the production of commodities. Leaving aside distributional considerations, we conclude that higher taxes should be imposed on market goods used in the production of `Eating' and lower taxes imposed on market goods used in the production of `Recreation'.
Keywords: H21; J22; D13; 330; Optimal taxation; Time use; Elasticity of substitution; Optimale Besteuerung; Haushaltsökonomik; Zeitverwendung; Substitutionselastizität; Mexiko